Surface Modification of TFC-PA RO Membrane by Grafting Hydrophilic pH Switchable Poly(Acrylic Acid) Brushes. (22nd May 2020) - Abbas, Muhammad Asad; Mushtaq, Shehla; Cheema, Waqas A.; Qiblawey, Hazim; Zhu, Shenmin; Li, Yao; Zhang, Runnan; Wu, Hong; Jiang, Zhongyi; Sadiq, Rehan; Ahmad, Nasir M.
Abstract : The grafting of pH-responsive poly(acrylic acid) (PAA) brushes was carried out on the surface of a commercial TFC-PA membrane using surface-initiated atom transfer radical polymerization (SI-ATRP). Poly(t-butyl acrylate) was polymerized through the SI-ATRP method followed by its acid hydrolysis to form PAA hydrophilic polymer brushes. Surface morphology, permeation flux, salt rejection, and pore sizes were investigated. The contact angle for water was reduced from 50° for a pristine membrane to 27° for the modified membrane due to a modification with the hydrophilic functional group and its brush on membrane surfaces. The flux rate also increased noticeably at lower pH values relative to higher pH for the modified membranes, while the flux remains stable in the case of pristine TFC-PA membranes. There is slight transition in the water flux rate that was also observed when going from pH values of 3 to 5. This was attributed to the pH-responsive conformational changes for the grafted PAA brushes. At these pH values, ionization of the COOH group takes place below and above p K a to influence the effective pore dimension of the modified membranes. At a lower pH value, the PAA brushes seem to permit tight structure conformation resulting in larger pore sizes and hence more flux. On the other hand, at higher pH values, PAA brushes appeared to be in extended conformation to induce smaller pore sizes and result in less flux. Further, pH values were observed to not significantly affect the NaCl salt rejection with values observed in between 98.8% and 95% and close to that of the pristine TFC-PA membranes. These experimental results are significant and have immediate implication for advances in polymer technology to design and modify the "switchable membrane surfaces" with controllable charge distribution and surface wettability, as well as regulation of water flux and salt.